IMPLEMENTASI NILAI-NILAI SPIRITUALITAS KRISTIANI KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN PROFESIONALISME GURU SD YPPK BILOGAI PAPUA (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This research is aimed at uncovering condition of christian spriritualism values in attemp to improve teachers profesionalism and its obstacles faced and its efforts done in increasing the quqlity of the education at Bilogai YPPK Elementay School, a Chatolic Education Fondation Owned by Timika Bishopric in the Regency of Intan Jaya, Papua .This research used qualitative approach and datum source consisting of the headmaster, the teachers, or the school committe, as well. Thr Research datum are collected and compiled through observations, interviews, documentations and triangulation. The datum are analysed with model analysis through datum reduction and conclution drawing. The datum validity is determined with triangulation, members checking and informen review.The result of the research shows that the values of christian spiritualism are implemented through role model and services to the teachers and the student in the headmaster’s leadership.This pattern can improve the teachers profesionalism to the fairly good level. Bisides that, in carring out their study tasks upon the students, it also emphasizes on the values of affection and sacrifice. The main obtacles faced by the headmaster in his efforts to improve the process quality and the education out put are dealt with its remote area and isolated region. Transportation and communication are quite diffcult to get and access in this remote area. The development and the increase of the quality of the education facilities and supporting facilities are hampered by the comunication systiem difficulty and the transportation difficulty. The headmaster is expected to keep on staying consistent integrating the christian spiritualism values in the leadership and to increase coordination and cooperation with the local goverment and the Catholik Ordos / The Conggregations of the Christians, especially in any matters dealing with the isolation breaking and the fund raising.